Screening and prevention of gynecologic malignancies in patients with lynch syndrome: following the guidelines - Ben David, Chen; Siegler, Yoav; Linder, Revital; Amit, Amnon; Matanes, Emad (Frontiers in Oncology, 2025)
Lynch syndrome (LS), a hereditary condition caused by germline mutations in mismatch repair (MMR) genes, significantly elevates the lifetime risk of endometrial cancer (EC) (40–60%) and ovarian cancer (8–10%) in affected women. Despite advances in colorectal cancer screening for LS patients, optimal strategies for gynecologic cancer prevention remain under debate. Current recommendations for EC surveillance, including annual transvaginal ultrasound and endometrial biopsy starting at age 30–35, lack robust evidence for effectiveness. Risk-reducing hysterectomy with bilateral salpingo-oophorectomy (BSO) is frequently advised after childbearing to mitigate cancer risk. Emerging data suggest that hormonal interventions, such as oral contraceptives and progestin-based therapies, may reduce EC risk by up to 50%, offering non-surgical preventive options. Lifestyle modifications, including weight management and physical activity, further complement risk reduction strategies. Molecular diagnostic advancements, including immunohistochemistry and microsatellite instability testing, enhance early identification of LS-associated gynecologic malignancies. For patients with advanced or recurrent EC, the integration of immunotherapy into treatment regimens has demonstrated significant efficacy. Agents such as pembrolizumab and dostarlimab, particularly in combination with carboplatin and paclitaxel, have improved progression-free and overall survival rates for patients with MMR-deficient tumors. This review highlights the need for personalized, evidence-based approaches to gynecologic cancer screening and prevention in LS, emphasizing the importance of integrating genetic testing, patient education, and novel therapeutic options. Future research should focus on refining screening protocols and expanding non-invasive preventive strategies to improve outcomes for this high-risk population.